How efficient is the U.K. housing market? - Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Extending the controversial findings from the relevant literature, the results from the quarterly transaction-based Nationwide indices from 1974 to 2009 provide further empirical evidence on the rejection of the weak-form version of efficiency in the U.K. housing market. In addition to conducting parametric and non-parametric tests, we apply technical trading strategies to test whether or not the inefficiencies can be exploited by investors earning excess returns. The empirical findings from the technical trading strategies support the results from the statistical tests and suggest that investors might be able to obtain excess returns from both autocorrelation- and moving average-based strategies compared to a buy-and-hold strategy for 10 out of 14 markets.
Keywords: G12; G14; G15; R31; 330; Housing market; weak-form market efficiency; random walk hypothesis; variance ratio tests; runs test; trading strategies; Wohnungsmarkt; Wohnimmobilien; Immobilienmarkt; Markteffizienz; Statistischer Test; Schätzung; Großbritannien